Pro IronPython - Harris, Alan (2012)
Python’s not the only game in town to use dynamic typing (also known as duck typing, which you will learn about in due time), but it did catch my eye and challenged my perspective as a programmer. “What is this? How does one accurately program anything in this fashion? Five hundred lines of code and not one duck! Python’s a liar.” A little unsettling, you can imagine.1